Industrial growth after import substitution: the Peruvian textile industry - Paus, Eva (1985)
​In this article the author explores the reasons behind the boom of textiles exports in Peru during the second half of the past decade. The main question she raises is if such exports were soleley determined by the management of commercial policy or if it is necessary to search for other explanatory factors. Her analysis leads her to conclude that important among the latter have been aspects such as the evolution of domestic demand, the degree of openness of the economy, the competitiveness of domestic production in world markets, the stability of the legal framework, and the attitude of the business community towards exports. The author thus gives us an integral vision of the export boom of the seventies by examining those aspects which normally remain hidden behind the process of commercial policy implementation.​